2022
DOI: 10.3390/ijerph191610454
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the 18-Year Threshold with Third Molars Radiographs in the Southern Italy Population: Accuracy and Reproducibility of Demirjian Method

Abstract: The estimation of the age of the majority of living subjects is widely required nowadays due to the presence of unidentifiable individuals, without documents and general information, involved in migration or legal procedures. Dental age estimation (DAE) is a valid method for investigating the age of subjects. The aim of this study was to evaluate the accuracy of the Demirjian method in a limited age group (16–24 years) in differentiating between older and younger than 18 years. From an initial sample of 17594 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Demirjian’s “eight stages” is the most commonly used method for estimating age from oral anatomical structures [ 5 , 6 ]. This is a very simple method for scoring bone calcification and maturity, but it has limitations that apply to children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demirjian’s “eight stages” is the most commonly used method for estimating age from oral anatomical structures [ 5 , 6 ]. This is a very simple method for scoring bone calcification and maturity, but it has limitations that apply to children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…A new scoring method that corrects and supplements this has been proposed, but it is unsuitable because of the high error in age estimation resulting from the subjective judgment of the observer; therefore, a study on a more accurate method is needed [ 7 , 8 ]. According to Caggiano et al [ 6 ], as a result of a study using third molar radiographs in a population in southern Italy, the accuracy and reproducibility of the Demirjian method were confirmed over 90%, but it was suggested that additional research on a larger study population is needed. Recently, an age estimation method based on the methylation level of DNA extracted from teeth using a real-time methylation-specific polymerase chain reaction was reported as evidence that DNA methylation in the human genome isolated from bodily fluids changes with age [ 9 ].…”
Section: Introductionmentioning
confidence: 99%